Strengthening workforce resilience to sustain community health services during crises: evidence from Chinese general practitioners - Guo, Botang; Li, Yongbin; Fu, Ying; Li, Minyao; Wang, Yue; Liu, Shuyu; Zhou, Yanjuan; Liu, Yu; Tang, Ping (Frontiers in Public Health, 2025)
BackgroundEnsuring the resilience and retention of the primary healthcare workforce is critical to maintaining health service continuity during public health crises. While pandemic preparedness frameworks increasingly emphasize integrated economic and health policies, the role of organizational and psychological factors in sustaining frontline health personnel has received less empirical attention. This study aimed to investigate the prevalence of turnover intention among community general practitioners (GPs) in Luohu District, Shenzhen, China, and to examine the mediating role of work engagement in the relationship between perceived organizational resilience and turnover intention.MethodsA cross-sectional survey was conducted among 927 community health physicians from Aug to Dec in 2024 in Luohu District, Shenzhen, a region where all community health centers are governed by a unified hospital group. Participants completed validated scales assessing organizational resilience, work engagement, and turnover intention. Descriptive statistics, correlation analysis, and hierarchical regression analysis were performed. The mediating effect of work engagement was tested using bootstrapping procedures, controlling for significant demographic and occupational covariates.ResultsA high prevalence of turnover intention was observed, with 65.16% of GPs reporting high or very high levels. Significant differences in turnover intention were found across age groups, professional titles, cadre status, monthly income, and perceived public health workload. Mediation analysis revealed that work engagement partially mediated the relationship between organizational resilience and turnover intention (B = −0.018, 95%CI [−0.070,–0.011] without covariates; adjusted indirect effect B = –0.019, 95%CI [−0.026,–0.012] with covariates), accounting for approximately 16.82% (17.12% adjusted) of the total effect. These relationships remained significant after controlling for covariates.ConclusionTurnover intention among community GPs in the studied region is alarmingly high, posing a significant challenge to workforce stability. Organizational and psychological resources play a key role in mitigating workforce attrition risks in community health systems. Strengthening organizational resilience and fostering work engagement may offer cost-effective, non-technological strategies to maintain essential health service delivery capacity during future pandemics, aligning with broader goals of economic stability and pandemic preparedness.